La CittÃ del Sapere: lâ€™Istituto di Botanica di Giuseppe Capponi (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
The Institute of Botany and Pharmaceutical Chemistry, at the Sapienza University of Rome Campus, built in 1932-1935 by Giuseppe Capponi, preserves, to date, the formal structure and the original function of the project. Commissioned by the Consorzio autonomo per lâ€™Assetto edilizio della Regia UniversitÃ  di Roma (Autonomous Consortium for the building organization of the Royal University of Rome), under the direction of Marcello Piacentini, it was built by the Federici Construction Company. Technological innovation, with the use of iron and glass, make this work the most avant-garde project of the University Campus, with clear links, in external readability, to industrial construction.